Management Of International Curriculum Adaptation as An Effort to Improve the Quality of Learning - Darmawan, Dendys (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to determine the adaptation management of the Al-Azhar Cairo curriculum at Al-Azhar Islamic Middle School Cairo Palembang in order to improve the quality of learning, starting from planning, implementing, evaluating, and following up on the results of the evaluation. This research method uses a qualitative approach with a case study type. The results of this study indicate that: 1) The international curriculum planning for Islamic Middle School Al-Azhar Cairo Pelembang involves foundations, teachers, Al-Azhar Cairo University, Cakrawala Insan Azhari Foundation, and Al-Azhar Cairo alumni education practitioners to adapt the Al-Azhar curriculum Cairo in the subjects of Islamic Religious Education, Arabic, and Tahfidz Qur'an; 2) The implementation of the international curriculum at Al-Azhar Islamic Middle School Cairo Palembang in its early stages was implemented as a whole with assistance from the Cakrawala Insan Azhari Foundation Jakarta; 3) The evaluation of the international curriculum carried out by foundations and schools after 1 year of implementing the curriculum shows that not all material from the Al-Azhar Cairo curriculum can be given 100% to students, due to, among other things, the language of instruction in PAI material books and Arabic, the target Tahfidz Qur'an, and focus on Arabic material content. 4) The follow-up of the curriculum in Arabic, PAI, and Tahfidz Al-Qur'an in the second year and so on is increasingly adapted to the conditions and needs of students and the vision and mission of the institution, including Arabic material which is more based on the thematics of daily conversations and Tahfidz Al Quran material is more adapted to the ability of each student in memorizing after an initial assessment of each student is carried out. This article is expected to provide additional insight for educators and decision makers in educational institutions in improving the quality of learning.